Pain in elite athletes - Neurophysiological, biomechanical and psychosocial considerations: A narrative review - Hainline, B.; Turner, J.; Caneiro, JP; Stewart, M.; Lorimer Moseley, G. (BMJ Group, 2017)
Pain is a common problem among elite athletes and is frequently associated with sport injury. Both injury and pain interfere with peak performance. Pain management should be based on the physiological, anatomical and psychosocial influences on the individual's pain and is not equivalent to injury management, which focuses on musculoskeletal recovery and return-to-play. This narrative review provides a foundation for understanding the differing causes and types of pain in elite athletes, thereby serving as a springboard for comprehensive pain management.